Allergic Fungal Sinusitis Imitating an Aggressive Skull Base Lesion in the Setting of Pembrolizumab Immunotherapy. (January 2021) - Krane, Natalie A.; Beswick, Daniel M.; Sauer, David; Detwiller, Kara; Shindo, Maisie
Objectives: We report a case of acutely worsening allergic fungal sinusitis in a patient receiving immunotherapy with pembrolizumab, a programmed cell death protein 1 (PD-1) inhibitor. Methods: A 53-year-old man with a history of metastatic melanoma and recent initiation of pembrolizumab therapy presented with acutely worsening headaches, left abducens nerve palsy, and neuroimaging demonstrating an erosive skull base lesion with bilateral cavernous sinus involvement. Results: Intraoperative findings were consistent with non-invasive allergic fungal sinus disease. Microbiology and histopathologic data ruled out malignancy and demonstrated Aspergillus fumigatus without concern for angioinvasion. After treatment with antifungal therapy, the patient's symptoms and abducens nerve palsy resolved. Symptoms were well-controlled 7 months after his initial presentation. Conclusions: Inflammatory sinusitis in patients receiving anti-PD-1 therapy may be secondary to T-cell infiltration, a similar pathophysiology as immune-related adverse events, and warrants appreciation by otolaryngologists given our increasing exposure to immunotherapy and its head and neck manifestations.